Annual report 1979 - Instituto Interamericano de Ciencias Agrícolas (IICA) (IICA, 2021)
This document presents information on tools for technical cooperation, institutional relations, participatory technical cooperation, IICA and information, documentation, agricultural communication, agricultural education, research and transfer of agricultural technology, promotion of agricultural production, regional rural development , structural change, IICA agricultural policy, Simón Bolívar fund, summary and financial analysis.